Picture Fuzzy Linguistic Sets and Their Applications for Multi-Attribute Group - Ashraf, S.; Mehmood, T.; Abdullah, S.; Khan, Q. (The Nucleus, 2018)
Â Having encouraged by the linguistic term in decision models, it is proposed a method of multi attribute group decision making. This amalgamates the idea of picture fuzzy sets and linguistic term sets to discourse the situations where the real-life problems fail to express in numerical form. Firstly, it is introduced the concept of picture fuzzy linguistic number and comparison rules for ranking the alternatives are discussed. Further the aggregation operators based on picture fuzzy linguistic information are introduced. Finally, it is introduced a technique to obtain satisfactory results about real-life complex problems, and it is given a descriptive example to discuss the reliability and effectiveness of the suggested technique by using group decision criteria. Subject classification: 03E72